COMPARATIVE STUDY OF ORGANIC MATTER DEGRADATION OF COMPOSTED SLUDGE AND SLUDGE LANDFILLED / ETUDE COMPARATIVE DE LA DEGRADATION DE LA MATIERE ORGANIQUE DES BOUES COMPOSTEES ET BOUES MISES EN DECHARGE - SLIMANE LAHSAINI; LEILA IDRISSI; SALAH SOUABI; LOUBNA EL FELS; ANAS AGUELMOUS; MOHAMED HAFIDI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The results of the biotransformation of organic matter for three trials A (500 kg sludge + 400 kg turf + 100 kg of straw), B (1000 kg sludge composted alone), and C (1000 kg sludge landfilled) after six months show a good degradation rate for trial A, compared to B, and C. C/N ratio decrease from 30 to 12 for mixture A, from 32 to 19 for B, and from 32 to 24 for C. An important decomposition rate, about 74 %, for mixture A has been reached after six months. The final compost for mixture A exhibited a high concentration (151.7 g·kg-1) of humic substance and a low concentration of heavy metal contents, compared to the AFNOR standard (NF U 44-041). The efficiency of the composting is confirmed by the germination index (GI), which exceeds 90 % for the trial A. However, phytotoxicity for trials B and C remains less important (GI does not exceed 40 %). The results of trial A will open the way for the agricultural use of sludge.